Random Deviations and Systematic Errors and Their Impact on Life Table Indicators - Cholakov, Nikola (Research Papers, 2005)
Statistical data processing of demographic information in Bulgaria seems to be excessively elongated and complicated - from the death reports through different local and central administrative units, the population register up to the national statistical authority. Such a transportation and exchange of information on different carriers through different departments might be a premise for errors and discrepancies of diverse nature which might affect even the most analytical indicators like those of the life tables. The risk of accidental, inaccurate or incorrect application of the corresponding methodologies of data processing should not be underestimated too.The problems of random deviations and systematic errors are examined in the study and a wide range of solutions are sought for the impact on the life table indicators both within the stochastics of the life table generation and the demographic processes in general as well as external to demography factors.In the process it is shown how some intermediate results could be used for comparative analysis of mortality using life table data bearing in mind the variability of the indicators due to different factors.